2006
DOI: 10.1111/j.1651-2227.2007.00025.x
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology and factors associated with nocturnal enuresis and its severity in primary school children in Taiwan

Abstract: Our investigation showed the prevalence of enuresis is similar to those reports from the north of Taiwan and most of other western countries, but higher than that of China and Hong-Kong. Difficulty in waking and time of wetting were the only factors significantly associated with the severity of enuresis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
39
4
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 27 publications
(41 reference statements)
13
39
4
2
Order By: Relevance
“…Consistent with previous population-based studies,1,3,6,8-10,12,19 we found a higher prevalence of enuresis and encopresis in boys than in girls and maximum prevalence at age 7-9 years, followed by a decline by 12 years of age. Contrary to previous clinical studies,34 but consistent with previous epidemiological studies,10 socioeconomic status was not associated with enuresis in the current study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous population-based studies,1,3,6,8-10,12,19 we found a higher prevalence of enuresis and encopresis in boys than in girls and maximum prevalence at age 7-9 years, followed by a decline by 12 years of age. Contrary to previous clinical studies,34 but consistent with previous epidemiological studies,10 socioeconomic status was not associated with enuresis in the current study.…”
Section: Discussionsupporting
confidence: 92%
“…According to the ICSS, enuresis or (intermittent) nocturnal incontinence is defined as at least one wet night per month. Higher rates of enuresis were observed in population-based epidemiological studies that applied the less stringent DSM-III criteria,4,5 ICD-10 criteria,12,15 or ICSS definition 6,13. In addition to different diagnostic criteria, differences in the age range and ethnicity of children and cultural differences may also explain the varying prevalence estimates of enuresis across different studies.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Second, the caregivers may be more aware and easier to access to healthcare in urban area 5. Consistent with previous population-based studies, the present study observed NE to be male-predominated, and associated with increased prevalence of other neurobehavioral problems 28 29. In the present study, the distribution of ADHD and NE were both found to be male and school-age predominant.…”
Section: Discussionsupporting
confidence: 90%
“…Level of parents education Our study showed non significant difference between cases and controls regarding the educational level of the parents .Some studies have reported parents of enuretics had low educational level [46,26,47,29] .Also in Iran the most recent study ,there was low educational level of fathers in 48.3% and 62.8% in mothers [19] in all that studies the educational level was classified in two categories only (Primary school or less and Junior high school or more ) in our study the educational level of the parents was classified to four categories which are more precise and more expressive(illiterate, read and write, moderate and university and higher) In Turkey Gur et al found a relation between enuresis and the low educational level of the fathers, but there study had no control group. [25] …”
contrasting
confidence: 48%